2015
DOI: 10.1007/s11240-015-0871-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for propagation of recalcitrant pistachio cultivars that sidesteps rooting by ex vitro grafting of tissue cultured shoot tips

Abstract: Pistachio (Pistacia vera L.) cultivars need to be grafted on suitable rootstocks for their propagation, but grafting success is uncertain, preventing producers to meet plant demand. Thus, there is a need for a better grafting method that in addition to increase success rate, allows us an early detection of success. Here, we have developed an alternative grafting technique that achieves these goals using young potted seedlings of terebinth rootstock and reduced size micropropagated scions from commercial cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The presented data confirmed that 1/2 MS media supplemented with IBA during 60 days had the best significant effect on the shoot elongation. Phloroglucinol (PG) is a phenolic compound that inhibits auxin oxidation and stimulates shoot and root growth (Pérez et al 2015;Marín et al 2016). The results of this study show a synergistic effect of phloroglucinol with IBA, an analog of auxin, which can be degraded by decarboxylation as reported by De Klerk et al 2011.…”
Section: Discussionsupporting
confidence: 64%
“…The presented data confirmed that 1/2 MS media supplemented with IBA during 60 days had the best significant effect on the shoot elongation. Phloroglucinol (PG) is a phenolic compound that inhibits auxin oxidation and stimulates shoot and root growth (Pérez et al 2015;Marín et al 2016). The results of this study show a synergistic effect of phloroglucinol with IBA, an analog of auxin, which can be degraded by decarboxylation as reported by De Klerk et al 2011.…”
Section: Discussionsupporting
confidence: 64%
“…This contrasting result might be explained by a different sensitivity to PGRs (type and concentration) offered by different genotypes or by carry-over effects from the multiplication phase, or else by a combination of both the factors. Indeed, in vitro rooting is considered genotype-specific within many woody fruit species such as almond [32], pistachio [33], and peach [34], among the others. On the other hand, Keresa et al [25] evaluated in vitro caper rooting efficiency as affected by the carry-over effect and evoked the role of CKs as auxin antagonists and their involvement in tuning auxin transport and biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of physiological disorders during micropropagation of certain species of Pistacia has been attributed to several causes as the culture media composition, the PGRs or the culture system 26,34,37,53–55 , but none of the studies focus on determining the causes of those disorders. We have paid attention to the physiological abnormalities that occurred during two independent micropropagation experiments of Pistacia carried out in our laboratory, recording and categorizing data related to several disorders to get insight about the causality of their appearance.…”
Section: Discussionmentioning
confidence: 99%
“…The vitamins-mixtures of original MS 10 , Gamborg B5 64 or DKW 31 are commonly added to the components of culture media used for micropropagation of Pistacia species 26,35,37,54,55,65 . The use of computer-based neurofuzzy logic has revealed a linear positive impact of pyridoxine-HCl and nicotinic-acid on promoting some shoot multiplication parameters of pistachio 52 , but, as far as we know, there is no demonstrative conclusion about the influence of vitamin on the physiological disorders occurred during in vitro culture of other woody species.…”
Section: Discussionmentioning
confidence: 99%